Altered arginine metabolism in colon cancer: a sign of increased proliferative potential of tumor-adjacent tissue - Branković, Branko; Stanojević, Goran; Veljković, Andrej; Kocić, Gordana; Nestorović, Milica; Đinđić, Boris; Bašić, Jelena; Stojanović, Ivana (Archives of Biological Sciences, 2022)
Paper description: Arginine metabolite levels and arginase activity in colon cancer tumors and adjacent tissues could have a predictive value in risk assessment for tumor growth and patient survival after surgery. Arginine metabolite concentrations and arginase activity were determined in colon cancer tumors and adjacent and healthy tissues post-surgery and linked to patient survival. Polyamine concentrations and arginase activity was significantly increased in cancer and adjacent tissues, indicating a high proliferative potential of tissue surrounding the tumor. This study provides a basis for understanding the possible predictive value of arginase activity in adjacent tumor tissue for its proliferative potential. Abstract: Colorectal cancer (CRC) is one of the most frequent forms of malignant tumors in the human population. The literature data about the role of arginine metabolism in CRC point out its double-faced role. In three tissue specimens of 50 patients who underwent surgical resection for colon adenocarcinoma (tumor, adjacent and healthy tissues more than 10 cm from the tumor border – at the incision margin) taken during surgery, polyamines and the concentration of NO2+NO3 and arginase activity were determined. Polyamine levels and arginase activity were significantly increased in cancer and adjacent tissue specimens compared to healthy ones, while the level of NO2+NO3 was significantly lower in cancer compared to both adjacent and healthy tissues. The high polyamine content in the adjacent colonic mucosa indicates a high proliferative potential of tumor-adjacent tissue. Although we found individual correlations indicating the possible prognostic value of arginase, the performed statistical analysis did not show a predictive significance of arginase activity in the examined tissue specimens for five-year survival of the patients. Nevertheless, the obtained results provide the rationale for further studies of arginine metabolism in tissue specimens after surgery in patients with CRC, which could be useful in the evaluation of the risk for tumor growth, recurrence, metastases and survival after surgical intervention.